#TITLE_ALTERNATIVE# - MAYNARD SIAHAAN (NIM 10202020); Pembimbing: Dr. Eng. Alamta Singarimbun, SAHALA
Earth self potential is produced by various sources without any current injection into the underground although the cause of the sources still can't be defined physically. This final assessment will talk about the phenomena of the self potential followed by the theoretical analysis, measurements, and data analysis. Generally, the final assessment discusses about the concept of self potential, started from the causing factors, the variety of self potential, until the measurements. Specifically, this paper discuss about the simple model of 2D shaped plate which is analyzed using the quantitative interpretation method. As a comparative data, this paper also makes experiments by burying an iron plat diagonally underneath the surface of the ground and by program simulation. The acquired result will show the influence of the self potential anomaly curve to the inclination, current intensity and medium resistivity, and depth of plat so it could be much easier when doing the remodeling of the self potential data afterward.